A framework for assessing the resilience of a disaster debris management system. (June 2018) - Kim, Jooho; Deshmukh, Abhijeet; Hastak, Makarand
Abstract: Disaster debris management plays a critical role in expediting the disaster recovery process. This study aims to present a framework for effective disaster debris management for a resilient community. The framework consists of a Geographical Information System (GIS) and system dynamics to assess debris removal performance. GIS was used to conduct a land suitability analysis for a temporary debris management site and system dynamics were applied to evaluate the debris removal performance in different scenarios. This systemic approach and quantitative analysis enable a decision maker to gain insights into the inter-relationship between critical infrastructure and resources, the effectiveness of temporary debris management sites, and the debris removal performance. Also, a debris management team would have benefits from the framework by being able to (1) understand dynamic behaviors of debris removal operation, (2) evaluate the existing debris management plan, and (3) set up multiple strategies for optimal debris removal operations under different disaster-impact scenarios.